Effects of blood pressure lowering on clinical outcomes according to baseline blood pressure and cardiovascular risk in patients with type 2 diabetes mellitus: the ADVANCE trial - Rahman, F; McEvoy, J; Ohkuma, T; Marre, M; Hamet, P; Harrap, S; Mancia, G; Rodgers, A; Rahman, F; Selvin, E; Williams, B; Muntner, P; et al. (American Heart Association, 2019)
The optimal blood pressure (BP) goal in patients with diabetes mellitus remains controversial. We examined whether benefits and risks of intensified antihypertensive therapy in diabetes mellitus are influenced by either baseline BP or cardiovascular disease (CVD) risk. We studied 10 948 people with diabetes mellitus, at moderate-to-high risk, in the ADVANCE trial (Action in Diabetes and Vascular Disease: Preterax and Diamicron Modified Release Controlled Evaluation). Cox models were used to determine whether baseline BP category or CVD risk modified the outcomes of combination perindopril-indapamide treatment, compared with placebo. During 4.3 years of follow-up, treatment with perindopril-indapamide versus placebo reduced mortality and major vascular (macrovascular or microvascular) events. There was no evidence of differences in these effects, regardless of baseline systolic BP (evaluated down to <120 mm Hg; P for heterogeneity, 0.85), diastolic BP (evaluated down to <70 mm Hg; P=0.49), or whether 10-year CVD risk was ≥20% or <20% (P=0.08). The effects of randomized treatment on discontinuation of treatment because of cough or hypotension/dizziness were also statistically consistent across subgroups defined by baseline BP and CVD risk (all P ≥0.08). Adults with diabetes mellitus appear to benefit from more intensive BP treatment even at levels of BP and CVD risk that some guidelines do not currently recommend for intervention.